Optimized Digital Twin for Flood Forecasting in the Ebro River - Vallés, Pablo; Echeverribar Pérez, Isabel; Garc´´ía-Navarro, Pilar; Brufau, Pilar (Jornada de Jóvenes Investigadores del I3A, 2023)
Year after year, floods cause high losses in several regions along the Ebro River. Therefore, it is necessary to develope tools based on numerical simulations to foresee the negative effects of these phenomena. Different strategies are proposed towards a digital twin of the river reach.